SOCIAL PEDAGOGICAL PRINCIPLES OF PREPARING STUDENTS FOR FAMILY LIFE (World Bulletin of Social Sciences, 2023)
Today's in the day Uzbekistan 62% of the population the children, teenagers, in short, up to 30 years old has been boys and girls, their known part while young families organize is enough. Young families are one of the important subjects of social-political, economic, cultural-spiritual renewal and development of the society, and they play an important role in influencing the complex processes taking place in social life and driving development. plays Therefore, at present , the deep and comprehensive analysis of the formation and development of the spiritual, moral and spiritual world of young families is of great importance from a scientific and practical point of view
Keywords: Children; teenagers; boys and girls